2015
DOI: 10.1155/2015/878535
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue-Derived Mesenchymal Stem Cells Exert In Vitro Immunomodulatory and Beta Cell Protective Functions in Streptozotocin-Induced Diabetic Mice Model

Abstract: Regenerative and immunomodulatory properties of mesenchymal stem cells (MSCs) might be applied for type 1 diabetes mellitus (T1DM) treatment. Thus, we proposed in vitro assessment of adipose tissue-derived MSCs (AT-MSCs) immunomodulation on autoimmune response along with beta cell protection in streptozotocin- (STZ-) induced diabetic C57BL/6 mice model. MSCs were extracted from abdominal adipose tissue of normal mice and cultured to proliferate. Diabetic mice were prepared by administration of multiple low-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…These results have implications for the treatment of chronic wounds as BM-MPCs not only promote neovascularization but also produce antiinflammatory cytokines that have the potential to advance chronic wounds past the chronic low-grade inflammation typically associated with poorly healing diabetic ulcers. [35][36][37] Several methods have previously been used to recruit endogenous progenitor cells, including injection of cytokines involved in stem cell homing, such as SDF or HGF, and gene therapy. 32,38 Polymeric hydrogels seeded with stem cells, however, display several advantages over these methods.…”
Section: Discussionmentioning
confidence: 99%
“…These results have implications for the treatment of chronic wounds as BM-MPCs not only promote neovascularization but also produce antiinflammatory cytokines that have the potential to advance chronic wounds past the chronic low-grade inflammation typically associated with poorly healing diabetic ulcers. [35][36][37] Several methods have previously been used to recruit endogenous progenitor cells, including injection of cytokines involved in stem cell homing, such as SDF or HGF, and gene therapy. 32,38 Polymeric hydrogels seeded with stem cells, however, display several advantages over these methods.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are stromal cells having the potential to differentiate along mesodermal cell lineages . Many studies have demonstrated therapeutic effects of MSCs in various inflammation‐associated diseases, such as acute kidney injury, arthritis, experimental autoimmune encephalomyelitis and diabetes . MSCs are considered a promising alternative treatment for IBD due to their unique immunomodulatory properties and ability to modulate tissue inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…Adipose derived mesenchymal stem cells are characterized by multi‐lineage differentiation potential and what is more the ability to regulate immune response . They exhibit the presence of specific surface markers including CD90 + , CD105 + , CD44 + and lack expression of CD45 − , elevated proliferative potential, viability, ability to self‐renew and clonogenic potential (CFU‐fs).…”
Section: Introductionmentioning
confidence: 99%
“…IL‐6 might seriously reduce ASC stemness. Besides multipotency, ASC exhibits immunomodulatory and immunosuppressive properties, which make them even more promising tool in cellular therapies , especially in the context of their potential clinical application in EMS treatment.…”
Section: Introductionmentioning
confidence: 99%